2022
DOI: 10.3390/jpm12050810
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Synovial Markers in Patients with Rheumatoid Arthritis and Periprosthetic Joint Infection

Abstract: Current diagnostic standards for PJI rely on inflammatory markers that are typically elevated in autoimmune diseases, thus making the diagnosis of PJI in patients with rheumatoid arthritis and joint replacement particularly complicated. There is a paucity of data on differentiating PJI from rheumatoid arthritis in patients with previous arthroplasty. In this study, we retrospectively analyzed the cases of 17 patients with rheumatoid arthritis and 121 patients without rheumatoid disease who underwent surgical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…[30][31][32][33] The cutoff values with the highest sensitivity and specificity for synovial fluid WBC and differential will facilitate the accurate diagnosis of infection after TJR in RA patients. A study by Ren et al 8 reported that in patients with chronic PJI, the optimal cutoff values of synovial fluid WBC and PMN% were significantly elevated in RA patients, showing acceptable-to-excellent discrimination. The results of this study showed that the optimal cutoff values of synovial fluid WBC and PMN% for diagnosing RA-PJI were higher than those of OA-PJI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32][33] The cutoff values with the highest sensitivity and specificity for synovial fluid WBC and differential will facilitate the accurate diagnosis of infection after TJR in RA patients. A study by Ren et al 8 reported that in patients with chronic PJI, the optimal cutoff values of synovial fluid WBC and PMN% were significantly elevated in RA patients, showing acceptable-to-excellent discrimination. The results of this study showed that the optimal cutoff values of synovial fluid WBC and PMN% for diagnosing RA-PJI were higher than those of OA-PJI.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the application of the conventional PJI diagnostic threshold for patients who have RA can lead to misdiagnosis, leading to incorrect treatment. 8 The current focus of research on the diagnosis of PJI includes markers such as alpha-defensin. [9][10][11] However, CRP, ESR, synovial fluid WBC, and PMN% are classical indexes for diagnosing PJI, which are economical and convenient to operate, so it is of great clinical importance to establish the thresholds of these common detection indexes for PJI diagnosis in patients who have RA.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has mainly focused on reliably diagnosing PJI with use of serum, synovial fluid, and intraoperatively collected implants 15 , 16 . Several authors have identified increased levels of inflammatory cytokines, such as IL-6, in the synovial fluid and serum 15 , 17 , 18 .…”
mentioning
confidence: 99%